Физико–химическое моделирование условий образования дисперсий магнетитов как агента удаления катионов из техногеннозагрязненных вод - Забулонов, Ю.Л.; Литвиненко, Ю.В.; Кадошников, В.М.; Писанская, И.Р. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
It is described in the article the use of magnetite dispersions as a coagulant for negatively charged sols. It is shown that the magnetite dispersions, synthesized from aqueous solutions in slightly alkaline medium, are good coagulants for negatively charged sols. The use of positively charged magnetite dispersions together with colloids of polysilicon acids gives possibility for applying this method for industrially polluted waters purification.